Breaking new ground: digging into TERRA function - Maicher, André; Lockhart, Arianna; Luke, Brian (Biochimica et biophysica acta. Gene regulatory mechanisms, 2014)
Despite the fact that telomeres carry chromatin marks typically associated with silent heterochromatin, they are actively transcribed into TElomeric Repeat containing RNA (TERRA). TERRA transcription is conserved from yeast to man, initiates in the subtelomeric region and proceeds through the telomeric tract of presumably each individual telomere. TERRA levels are increased in yeast survivors and in cancer cells employing ALT as a telomere maintenance mechanism (TMM). Thus, TERRA may be a promising biomarker and potential target in anti-cancer therapy. Interestingly, several recent publications implicate TERRA in regulatory processes including telomere end protection and the establishment of the heterochromatic state at telomeres. A picture is emerging whereby TERRA acts as a regulator of telomere length and hence the associated onset of replicative senescence in a cell. In this review we will summarize the latest results regarding TERRA transcription, localization and related function. A special focus will be set on the potential role of TERRA in the regulation of telomere length and replicative senescence. Possible implications of increased TERRA levels in yeast survivors and in ALT cancer cells will be discussed.